EBIRA CLOTH AND SOUTHERN NIGERIAN TEXTILE TRADITIONS (2012)
Ebira cloth weaving has, in the past, been relegated in the study of Nigerian textile traditions. Quite a number of scholars have worked on the Ebira traditional fabrics popularly referred to as Okene cloth which is quite unique in Nigerian weaving traditions. None of them has focused on the combined examination of the Ebira textiles with other cloth weaving cultures in Nigeria. This study, therefore, examines the Ebira cloth weaving tradition alongside those of the major cloth weaving communities in Southern Nigeria. The study adopted both primary and secondary methods of data collection. Primary data were collected through in-depth interview (IDI). Thirty interview sessions were conducted with twenty professional cloth weavers, six traders and three Directors of cloth weaving centres. Participant observation and key informant technique were also adopted. Photographs of some selected textile materials were taken and analysed. Secondary data were gathered through content analyses of relevant textbooks, academic journals, periodicals, magazines, theses and dissertations. Historical and anthropological approaches were used to analyse the major textile traditions of the Ebira in Okene, Ogaminana, Ukpogoro, Usungwe and those of Southern Nigerian communities from, Iseyin, Oyo, Owo, Ijebu-Ode, Abakaliki, Oshimili and Akwete. Ebira cloth is essentially woven on the broad loom, and contrasts with the Yoruba narrow-strip loom. Consequently, it is wider, more graphic and more complex in pattern designs than other fabrics of Southern Nigeria. Until synthetic fibres were introduced at the beginning of the 20th century, weavers used natural fibres such as bast and cotton to weave cloths. Nowadays, materials for Ebira-Tao and the Southern Nigerian textiles include cotton, silk and a range of rayon, lurex and industrially produced dyes. Ebira and Southern Nigerian traditional fabrics, whether rough or smooth, embellished with simple or intricate decorative designs are appraised on the basis of the communicative symbolisms contained within their physical forms. Due to the enlightenment of the people, the traditional beliefs attached to the symbolic significance of certain cloth patterns in Ebiraland and Southern Nigeria, are no longer strictly observed. It is, therefore, the end use of a piece of cloth that determines the design. Each material whether used as the base or as part of the decoration, gives the weavers the scope to weave different textile forms. The cultural significance attached to cloths in Ebira and Southern Nigeria are specific to their producers and not bound by general interpretations. The forms, styles and patterns of cloths have, over the years, been carefully developed to produce the unique characteristics of the Ebira fabrics. The uniqueness of Ebira cloth weaving tradition has given it a distinctive characteristic among the various traditional textiles in Nigeria. Through practical approach, the tradition should be sustained in order to increase its awareness and understanding. Documentation of the various aspects of the Ebira culture particularly its textile tradition, should be intensified to promote the peoples cultural values and identity. To enhance the social and cultural bonds among the Ebira and other Nigerians, further studies on Ebira culture and traditions should be encouraged.